Échelles territoriales et politiques du métabolisme urbain : la structuration des filières de biodéchets et l’intégration de l’agriculture urbaine à Rennes - Jean-Baptiste Bahers (Éditions en environnement VertigO, 2018)
This article underlines the circular economy’s issues related to the framework of urban metabolism, focusing the organic material and waste chain. It is about of combining the analysis of flows and their governance. It is based on a case study : the organic waste and material stream of Rennes. In this article, we have focused our analysis on bio-waste sectors. In particular, we have deepened its structuring through the analysis of three main aspects : practices, flows and public policies. The analysis reveals that are three main waste chains that coexist, with very different configurations : the "dominant" sector (composting platform, incineration, burial) ; the "participatory" sector (participatory composting) and the "future" chain (waste sorting, methanisation). This context shows that there is no real challenge to the centralized management of waste networks, but rather a hybridization of those chains.